Sacred Terror : Religion and Horror on the Silver Screen - Cowan, Douglas E. (Book collections on Project MUSE., 2008)
"Why do religious elements so often lurk at the heart of horror films? And why do they scare us so? In this book, Douglas Cowan argues that horror films are opportune vehicles for externalizing the fears that lie inside our religious selves: fear of evil; of the flesh; of sacred places; of death, dying badly, or not remaining dead; and of the power - and powerlessness - of religion."--Jacket.